2011
DOI: 10.1002/app.35626
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical properties and structure of in situ cured polyurethane/hydrogenated nitrile rubber compounds: Effect of carbon black type

Abstract: A peroxide-curable hydrogenated nitrile rubber (HNBR) was modified by in situ crosslinked polyurethane (PU) in a 1 : 1 weight ratio. PU was formed from solid PU precursors, polyester polyol, and blocked polyisocyanate incorporated in the HNBR during the curing of the latter. HNBR/PU blends containing carbon black (CB) of different types (N234, N330, and N550) were prepared in this work. Thirty parts of CB per hundred parts of polymer matrix (HNBR and PU) were used. The curing of PU was followed by differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…10 shows DSC analyses of virgin HNBR and HNBR specimens which had been aged for 3, 6 and 12 weeks at 160 C. These results show a thermal transition in the virgin HNBR in the region of À20 C, which is similar to the T g of the HNBR measured by DMA. It has been reported that glass transition temperature generally increases with acrylonitrile content [31], and a single endothermic step is typically reported for other HNBRs [21,32,33]. As seen previously in dynamic mechanical data (see Fig.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 72%
See 1 more Smart Citation
“…10 shows DSC analyses of virgin HNBR and HNBR specimens which had been aged for 3, 6 and 12 weeks at 160 C. These results show a thermal transition in the virgin HNBR in the region of À20 C, which is similar to the T g of the HNBR measured by DMA. It has been reported that glass transition temperature generally increases with acrylonitrile content [31], and a single endothermic step is typically reported for other HNBRs [21,32,33]. As seen previously in dynamic mechanical data (see Fig.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 72%
“…The HNBR used in this study also incorporates 50phr of HAF N-330 carbon black (26e30 nm primary particle diameter [20]), which is routinely included in commercial products to increase mechanical properties, abrasion resistance and environmental stability. It has been shown that N-330 is not the optimum carbon black in terms of effectively reinforcing HNBR [21], and nanoplatelet type fillers can reinforce even more efficiently if dispersed and oriented appropriately [13,14,22,23]. Therefore, this HNBR formulation was not designed to be the highest performing HNBR conceivable, but rather an HNBR which is representative of materials typically applied in subsea oilfield applications.…”
Section: Methodsmentioning
confidence: 95%
“…It is possible to influence the morphology and therefore the mechanical properties by various parameters such as (i) the chemical nature of polymers, (ii) compatibility of the components, (iii) weight fraction of the components, (iv) curing degree, (v) chain mobility to undergo phase separation, (vi) the relative rates of the competing kinetic processes and (vii) additional fillers. [93,107,112,113] Figure 13. DMA curve of XNBR, PMMA, a polymer blend and an IPN.…”
Section: Tailoring Of Mechanical Properties With Resinsmentioning
confidence: 99%
“…However, upon the addition of CB the PU domain size was reduced, which altered the overall phase structure of the composite. [113] For EP/SBR composites, the addition of CB also resulted in a morphology change of the compound. Whilst the pure EP sample depicted a cone-shaped fiber network, the morphology changed to irregular, spherical particles upon the addition of a filler.…”
Section: Tailoring Of Mechanical Properties With Resinsmentioning
confidence: 99%
“…Particularly, blending of polyurethanes with rubber and specifically with nitrile rubber has attracted attention due to the possible synergistic performance owing to their polar characteristics . However, the reported rubber/polyurethane blends have primarily been obtained by very high temperature melt‐ and/or time consuming solution‐blending of nitrile rubber with either pre‐synthesized polyurethane or solid polyurethane precursors (polyol and blocked polyisocyanate) or polyurethane synthesized in rubber solution …”
Section: Introductionmentioning
confidence: 99%